Comparison of Ceramic-on-Ceramic vs. Ceramic-on-Polyethylene for Primary Total Hip Arthroplasty: A Meta-Analysis of 15 Randomized Trials - Fang, Yan; Shang, Xiaobin (Frontiers in Surgery, 2021)
Abstract Objectives: This meta-analysis aimed to compare ceramic on ceramic (COC) components and ceramic on polyethylene (COP) components during THA. Settings: A meta-analysis of randomized controlled trials (RCTs) comparing COC and COP during primary THA was conducted. Electronic searches were current to March 2021. Participants: Trials were included for meta-analysis if they compared at least the bearing surfaces of COC and COP for patients undergoing primary THA if they reported the outcomes of THA after a certain period of follow-up, and only RCTs in English were included. Primary and secondary outcome measures: The primary endpoints consist of audible noise, prosthesis fracture, and revision. Second endpoints include dislocation, deep infection, osteolysis, and prosthesis loosening. Extracted data were statistically analyzed with the stata11.0. Results: A total of 15 RCTs containing 2702 patients (2813 hips) were included in the study. The audible noise (RR= 5.919, 95%CI: 2.043, 17.146; P ≤ 0.001) and prosthesis fracture (RR= 35.768, 95%CI: 8.957, 142.836; P = 0.001) were significantly higher in the COC group. Hip function, revision rate, dislocation rate, deep infection rate, osteolysis rate, and prosthesis loosening rate were comparable between these two groups, while the wear rate was higher in the COP group. Conclusion: The present result indicated comparable outcomes of COC and COP bearing surfaces in primary THA, high-quality RCTs with a long-term follow-up are still urgently needed to up to provide more evidence on the optimal bearing surfaces in primary THA.